ID 99 – Functional connectivity study on repetitive transcranial magnetic stimulation for central post-stroke pain. Issue 3 (March 2016) - Hosomi, K.; Shimizu, T.; Maruo, T.; Watanabe, Y.; Khoo, H.M.; Tani, N.; Goto, Y.; Kishima, H.; Yoshimine, T.; Saitoh, Y.
Abstract : Objective: Central post-stroke pain (CPSP) is one of the most refractory chronic pain syndromes. We and others have reported that repetitive transcranial magnetic stimulation (rTMS) of the primary motor cortex relieves pain in patients with CPSP. However, the mechanism underlying the pain relief remains unclear. This study aimed to investigate functional connectivity specific to CPSP and functional connectivity alteration associated with pain relief by rTMS. Methods: Subjects were 12 patients with CPSP and 12 age-matched healthy controls. Resting-state function MRI (rs-fMRI) was taken before and after 5 Hz-rTMS of the ipsilesional primary motor cortex in patients, meanwhile rs-fMRI was taken once in controls without the rTMS intervention. rs-fMRI data was preprocessed, and second-level analyses of seed-to-voxel connectivity were implemented. Results: The functional connectivity related to the ipsilesional primary motor cortex (FC-M1) was larger in patients than in controls. The alteration of FC-M1 after rTMS negatively correlated with pain relief. Conclusions: Our findings suggested that alteration of the functional connectivity might be one of the mechanisms underlying pain relief by rTMS in CPSP. Key message: rTMS might affect the functional connectivity related to the stimulation site in patients with CPSP.